Analisis Faktor Risiko yang Berhubungan dengan Kejadian Plasenta Previa di RSIA Ananda Makassar - Annisa Dwi Kemalahayati; Henny Fauziah; Miswani Mukani Syuaib (Universitas Islam Negeri Alauddin Makassar, 2025)
Placenta previa is a pregnancy complication that causes bleeding after 20 weeks. Bleeding is the leading cause of maternal deaths, accounting for 28%, so it is essential to identify risk factors of placenta previa. The purpose of this study is to determine the relationship between maternal age, interdelivery interval, history of caesarean section, and history of abortion with the incidence of placenta previa. This research uses a case-control study with an observational analytic approach. The case group sample was 120 respondents, and the control group was 120. The samples taken were under the inclusion criteria. The research instrument was the mother's medical records at the Ananda Mother and Child Hospital Makassar in 2020-2021. Data were processed with univariate and bivariate tests. Bivariate analysis test results obtained p-value = <0.001 for the relationship between maternal age (OR = 7.828), enter delivery interval (OR = 8.143), history of caesarean section (OR = 4.955) and history of abortion (OR = 3.769), and the incidence of placenta previa. There is a significant relationship between maternal age, interdelivery interval, history of caesarean section, and history of abortion with the incidence of placenta previa at Ananda Mother and Child Hospital Makassar.